New Developments in Prokinetic Therapy for Gastric Motility Disorders - Camilleri, Michael; Atieh, Jessica (Frontiers in Pharmacology, 2021)
Prokinetic agents are medications that enhance coordinated gastrointestinal motility and transit of content in the gastrointestinal tract, mainly by amplifying and coordinating the gastrointestinal muscular contractions. In addition to dietary therapy, prokinetics are the first line therapy to improve gastric emptying and symptoms, balancing benefits and risks of treatment. The Food and Drug Administration (FDA) of the United States recommends use of metoclopramide for less than 12 weeks’ duration due to the risk of reversible or irreversible extrapyramidal side effects. Domperidone can be prescribed through the FDA’s Expanded Access to Investigational Drugs Program. Macrolides are used off label and are associated with tachyphylaxis and variable duration of efficacy. Aprepitant relieves some symptoms of gastroparesis. There are newer agents in the pipeline targeting diverse gastric (fundic, antral and pyloric) motor functions, including novel 5-HT4 agonists, D2/3 antagonist, NK1 antagonist, and ghrelin agonist. Novel targets with potential to improve gastric motor functions include the pylorus, macrophage/inflammatory function, oxidative stress, and neurogenesis. In the current review, we discuss the use of pharmacological approaches with potential to enhance motor functions in the management of gastroparesis.